ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP DANA DEPOSITO PADA BANK UMUM KONVENSIONAL DI INDONESIA - Dessy Widya Rosvitasari; Munawar Ismail (Jurnal Ilmiah Mahasiswa FEB, 2014)
Deposit is one of the largest funding source for banks. The amount of deposit can be affected by bank internal and external factors. The research attempts to identivy the effect of external factors (macroeconomics variables) to fund of deposit in conventional banks. Macroeconomics variables that used in this research are Gross Domestic Product (GDP), SBI Rate, Inflation, and Exchange Rate for period 2005.1 – 2014.4. By using Ordinary Least Square (OLS), the result showed that only GDP and SBI rate that have significant effect to fund of deposits, however inflation and exchange rate have no effect to fund of deposits in conventional banks. Key words: Fund of Deposit, GDP, SBI Rate, Inflation, Exchange Rate, OLS.